ANALISIS KEMAMPUAN BERPIKIR KREATIF DALAM MENYELESAIKAN SOAL OPEN ENDED MATERI PENJUMLAHAN BILANGAN CACAH KELAS III SDN PUCANGSARI II - Wahyu Andreansya; I Ketut Suastika; Sri Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Creative thinking skills are highly emphasized in 21st century learning. Creative thinking is the process of finding new ideas that are still in the mind and have not been realized. Creative thinking skills have a function so that students will be more active and creative in developing ideas and solving various problems. Problems were found in class III of SDN Pucangsari, namely the difficulty of students developing diverse and creative answers, and some students hesitated in giving answers because they were afraid of being wrong or were not sure about their own thoughts. The purpose of the study was to determine how creative thinking skills were in solving open-ended questions on the addition of integers for class III of SDN Pucangsari II. The method used was descriptive qualitative. Data collection techniques were through tests and interviews. Data analysis techniques used qualitative Milles and Huberman. Based on the analysis of the data results, it can be stated that the level of creative thinking skills of class III students of SDN Pucangsari II on the originality thinking indicator was lacking. It can be seen that S-1 fulfills the original thinking ability (originality) and S-6, S-9, S-12 do not fulfill the original thinking ability (originality) because they are not careful in reading the instructions in the questions, so they do not provide unique thoughts and are not similar to other people in all questions.